Implementasi Kebijakan Program Badan Penyelenggara Jaminan Sosial Kesehatan Di Kecamatan Durai Kabupaten Karimun - Nurpaliza Nurpaliza; Edy Akhyari; Okparizan Okparizan (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
This study discusses the Implementation of Health Insurance Administration Agency Policies at the Durai District Health Center, Karimun Regency. This research refers to the policy implementation model of the Van Metter and Van Horn models, with variables of policy size and objectives, resources, characteristics of implementing agents, attitudes/dispositions of implementers, inter-organizational communication and implementing activities. The data collection techniques are carried out by observation, interviews, and documentation. The data obtained was then analyzed using steps including data collection, data reduction, data presentation, and drawing conclusions. The results showed that the implementation of the Health Social Security Administering Body Program Policy at the Durai District Health Center, Karimun Regency was not optimal and there were still deficiencies that still needed to be corrected. The arrangement of human resources should run optimally so that the program can continue running, there are still gaps in the use of infrastructure in obtaining free health services, and there are still poor people who have not yet received a BPJS card. The Durai Health Center as the executor of the BPJS program is expected to further intensify socialization regarding free h8ealth services, for example by conducting counseling and placing banners so that information about the BPJS program can reach remote villages.